2016
DOI: 10.5455/ijmsph.2016.26022016397
|View full text |Cite
|
Sign up to set email alerts
|

An assessment of the functioning of the Village Health Sanitation and Nutrition Committee in the rural areas of Kamrup district, Assam

Abstract: Background: The Village Health Sanitation and Nutrition Committee (VHSNC) is a first step toward decentralized planning and community empowerment approach Objective: To assess the constitution of the VHSNCs, to assess the activities undertaken by them, and to assess the funding and utilization status of the VHSNCs. Materials and Methods: Study design-Community-based cross-sectional study. Study place-Three blocks of Kamrup district viz, Boko-Bongaon, Hajo, and Sualkuchi. Study period-July 1 to October 31, 2015… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…[ 14 ] Similarly, another study from Assam also showed that around only 17% of the VHSNCs had conducted regular monthly meetings in the assessed year. [ 15 ] The present study evidence that the meetings of VHSNCs were not done in a serious mode.…”
Section: R Esultsmentioning
confidence: 55%
“…[ 14 ] Similarly, another study from Assam also showed that around only 17% of the VHSNCs had conducted regular monthly meetings in the assessed year. [ 15 ] The present study evidence that the meetings of VHSNCs were not done in a serious mode.…”
Section: R Esultsmentioning
confidence: 55%
“…It was identified that the understanding about the role of VHSNC was highest among ANMs, AWWs and ASHA workers. Das et al 13 also reported that there was a lack of clarity about the roles and responsibilities among VHSNC members. Srivastava et al 10 noted that a detailed training was imparted to ASHAs and AWWs, while others received only a brief orientation, which many, did not consider as ‘training’.…”
Section: Village Health Sanitation and Nutrition Committees (Vhsncs):...mentioning
confidence: 99%
“…Regularity in meetings : As per NHM, each VHSNC should organize monthly meetings, as it is during the meetings that the problems are identified, discussed and plans charted out for their mitigation 7 . However, irregularities in the monthly meetings of VHSNCs were observed, where the committees struggled to organize regular meetings and with full attendance 9 - 11 , 13 . Semwal et al 16 mentioned that among all 18 VHSNCs, meetings were not organized regularly.…”
Section: Village Health Sanitation and Nutrition Committees (Vhsncs):...mentioning
confidence: 99%
See 1 more Smart Citation